Trichological Analysis on Hair of Sahiwal Cattle - Rawat P; Gupta S K; Pandey Y; Shukla B P; Shrivastava N (Indian Journal of Veterinary Anatomy, 2026)
For trichological analysis guard hair from back, neck, umblical and tail regions of sahiwal cattle were collected. The colour, shape and band pattern of hair was examined to know the gross profile of hair. The cuticular impressions were prepared in a thin gelatin layer on a clean glass slide for assessment of cuticular scale pattern. For medullary configuration observation hair specimen was prepared with xylene. The physical characteristic of hair like colour, shape and band pattern showed huge variation in the same individual from region to region. The hair of sahiwal cattle were flat in all body regions.Microscopically the hair was composed of cuticle, cortex and medulla from outer to inner side. The cuticular scales were in the form of regular waves with smooth margin in back, neck and tail region and crenate margin in umbilical region. Hair medulla was continuous in back region but in neck, umbilical and tail regions it was fragmented. The margins of the medulla in all the body regions were scalloped type except in tail region where it was smooth. The medullary index was more than half, it showed that the medulla form more diameter of hair than the cortex.